2014
DOI: 10.1371/journal.ppat.1004134
|View full text |Cite
|
Sign up to set email alerts
|

Suppressor of Cytokine Signaling 4 (SOCS4) Protects against Severe Cytokine Storm and Enhances Viral Clearance during Influenza Infection

Abstract: Suppressor of cytokine signaling (SOCS) proteins are key regulators of innate and adaptive immunity. There is no described biological role for SOCS4, despite broad expression in the hematopoietic system. We demonstrate that mice lacking functional SOCS4 protein rapidly succumb to infection with a pathogenic H1N1 influenza virus (PR8) and are hypersusceptible to infection with the less virulent H3N2 (X31) strain. In SOCS4-deficient animals, this led to substantially greater weight loss, dysregulated pro-inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
69
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 63 publications
8
69
0
Order By: Relevance
“…SOCS4 belongs to the SOCS family that is composed of eight members, including cytokine-inducible Src-homology 2 protein (CIS), as well as SOCS1 to 7 (22,23). These proteins are known to be cytokine-inducible negative regulators of cytokine signaling, as well as key regulators of innate and adaptive immunity (24). Galic et al (25) also reported that the SOCS family proteins serve an critical role in mediating inflammatory responses in immune cells and metabolic organs.…”
Section: Discussionmentioning
confidence: 99%
“…SOCS4 belongs to the SOCS family that is composed of eight members, including cytokine-inducible Src-homology 2 protein (CIS), as well as SOCS1 to 7 (22,23). These proteins are known to be cytokine-inducible negative regulators of cytokine signaling, as well as key regulators of innate and adaptive immunity (24). Galic et al (25) also reported that the SOCS family proteins serve an critical role in mediating inflammatory responses in immune cells and metabolic organs.…”
Section: Discussionmentioning
confidence: 99%
“…Airway epithelial cells are the primary targets for influenza virus infection, and upon infection, they produce important levels of inflammatory cytokines (40). Interestingly, the treatment of human bronchial epithelial cells with ILG significantly reduced the expression of the inflammatory cytokines induced after influenza virus infection.…”
Section: Discussionmentioning
confidence: 99%
“…Defect of control of cytokine synthesis and activity (possible development of the "cytokine storm") [27,36] …”
Section: Socs4mentioning
confidence: 99%
“…The risk of severe influenza infection control of the activation of proinflammatory cytokines synthesis [36]. The interest in the genetic control of these processes is natural.…”
Section: Complex Of Se -Dependent Enzymesmentioning
confidence: 99%
See 1 more Smart Citation